AMINA WADUD’S FEMINIST HERMENEUTICS ON GENDER VERSES AND ITS IMPLICATIONS FOR ISLAMIC EDUCATION - Addzaky, Khoirul Umam; Alfani, Ilzam Hubby Dzikrillah; Rifai, Masyhuri (EL-MAQRA', 2026)
This study examines Amina Wadud’s feminist hermeneutics of gender-related verses in Sūrah al-Nisā’ through a comparative analysis with the classical exegesis of al-Ṭabarī, Ibn Kathīr, and al-Qurṭubī. The research employs a qualitative library-based method using a critical feminist hermeneutical approach. The analysis focuses on Q. 4:1 concerning creation, Q. 4:34 on qawwāmah, and Q. 4:11–12 on inheritance. The findings reveal that Wadud interprets these verses through contextual, linguistic, and ethical approaches emphasizing justice, equality, and relational responsibility. In contrast to classical interpretations that tend to frame gender relations hierarchically, Wadud distinguishes between the Qur’an’s universal moral values and historically conditioned social constructions embedded in interpretation. The study further demonstrates that feminist hermeneutics has significant implications for Islamic education, particularly in promoting critical hermeneutical literacy, dialogical learning, and more contextual and inclusive Qur’anic curricula.